KARAKTER EROPA PADA RUMAH TINGGAL SAUDAGAR BATHIK DI LAWEYAN SURAKARTA - Joko Daryanto, Tri (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Laweyan village has existed since the beginning of Nagari Surakarta Hadiningrat in 1745. It is such as a village ofbathik merchant with specific architectural characteristics. The character forms a merger of many architectural styles, which is dominated by Europhean (Western) style whithout disapearing Javanese architectural characteristics. In order to understand the using of European architectural elements, the research is performed by naturalistic approach. The samples and themes are defined on the field purposively. The finding of the themes is connected inductively in order to get the ideographic construction as localfinding. , The research founds the using ofgolden section in defining building sshape proportion and arranging its facade composition. The European forms and ornaments consist ofArt deco, Art nouveau, Greek and Indies which are merged in Javaneseformat eclectically. There is tendency that European forms and ornaments arefound in the rooms or part ofbuilding with visual continuity positions.